Implementasi Program Sanggar Lentera dalam Upaya Meningkatkan Kemampuan Membaca Anak di Majidi: Implementation of the Sanggar Lentera Program in an Effort to Improve Children's Reading Skills in Majidi - Mahfudz Shobirin; Nabila Nur Aulia; Muhammad Jihadul Khairi Rizki; Ahmad Ansori; Melina Sari (Elevasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2026)
The Sanggar Lentera program is one of the community service activities conducted in Majidi, focusing on improving reading skills among children who are not yet fluent. This study aims to describe the implementation of the reading class and the development of children’s reading abilities throughout the program. The research employed a descriptive qualitative method, with data collected through direct observation of learning activities, children’s responses, and changes in their reading skills across each meeting. The subjects consisted of ten children who experienced difficulties in recognizing letters and forming simple words. The program was conducted in seven sessions, although one meeting was canceled due to heavy rain, resulting in six effective sessions. The findings show that during the initial meeting most children were still at a basic stage of reading ability. However, through gradual reading activities, simple literacy games, and personalized guidance, the children began to show noticeable progress. They became more confident in trying to read, recognized letters more quickly, and were able to form simple syllables. Challenges encountered during the program included irregular attendance and children’s difficulty in maintaining focus. Nevertheless, the Sanggar Lentera program proved to have a positive impact on the children’s reading skills while creating a supportive and enjoyable learning environment. These results indicate that community-based nonformal learning approaches have the potential to serve as an effective complementary support for children who need foundational literacy assistance.